HIV‑1 drug‑resistance mutations and related risk factors among HIV‑1‑positive individuals receiving first-line antiretroviral therapy (Universa Medicina, 2025)
BackgroundAcquired immunodeficiency syndrome (AIDS) remains a global health issue. Antiretroviral therapy (ART) controls HIV progression, but widespread use had led to drug resistance mutations (DRMs) such as M184V and K103N, compromising treatment efficacy. This study assessed the prevalence of these mutations and identified associated risk factors in patients with first-line nucleoside reverse transcriptase inhibitor (NRTI)-based ART.MethodsA cross-sectional study was conducted involving 80 HIV patients aged > 18 years who had been on NRTI and non-NRTI (NNRTI) therapy for >6 months. Data included sociodemographic characteristics, ART adherence, opportunistic infections, viral load, CD4 count, treatment duration, ART regimen, and presence of M184V and/or K103N mutations. Genetic analysis was performed and statistical associations were assessed using simple and multivariate logistic regression.ResultsM184V and/or K103N mutations were detected in 8 patients (10%), significantly associated with poor ART adherence (p